2016
DOI: 10.3390/molecules21060706
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Characterizing the Complicated Sequential Metabolism of Salidroside in Rats

Abstract: Metabolic study of bioactive compounds that undergo a dynamic and sequential process of metabolism is still a great challenge. Salidroside, one of the most active ingredients of Rhodiola crenulata, can be metabolized in different sites before being absorbed into the systemic blood stream. This study proposed an approach for describing the sequential biotransformation process of salidroside based on comparative analysis. In vitro incubation, in situ closed-loop and in vivo blood sampling were used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…p-Tyrosol sulfate was the predominant metabolite identied in the hepatic metabolism of SAL, which accounted for over 50% of the total metabolites in systemic circulation. 10,11 The formation rate of p-tyrosol sulfate could therefore serve as an indicator for the hepatic metabolic rate of SAL. The liver S9 fraction (RLS) derived from 5 normoxic rats and 5 hypoxic rats were prepared respectively according to previously mentioned method.…”
Section: Assessing the Hepatic Metabolism Of Sal Under Hypoxia And Nomentioning
confidence: 99%
See 2 more Smart Citations
“…p-Tyrosol sulfate was the predominant metabolite identied in the hepatic metabolism of SAL, which accounted for over 50% of the total metabolites in systemic circulation. 10,11 The formation rate of p-tyrosol sulfate could therefore serve as an indicator for the hepatic metabolic rate of SAL. The liver S9 fraction (RLS) derived from 5 normoxic rats and 5 hypoxic rats were prepared respectively according to previously mentioned method.…”
Section: Assessing the Hepatic Metabolism Of Sal Under Hypoxia And Nomentioning
confidence: 99%
“…7a and b). 10,11 It was noticed that the formations of p-tyrosol sulfate were only dramatically inhibited when SAL was incubated with RLS in the presence of CBG inhibitor, suggesting the potential roles of CBG in the deglycosylation of SAL in rats. Moreover, the formations of p-tyrosol sulfate were signicantly inhibited when p-tyrosol was incubated with RLS in the presence of SULT2A1 inhibitor, suggesting the potential roles of SULT2A1 in the sulfation of SAL in rats.…”
Section: Enhanced Absorption Of Sal In Hypoxicmentioning
confidence: 99%
See 1 more Smart Citation
“…The nine metabolic pathways of poliumoside were proposed as rearrangement, reduction, hydroxylation, hydration, dehydration, methylation, acetylation, hydrolyzation, and sulfation, 216 which are partly in accordance with the result of Deng et al 215 Metabolites of salidroside in rats plasma samples indicated that salidroside was metabolized through glucuronidation, deglycosylation, sulfation, methylation, hydroxylation, and dehydroxylation in vivo. 217 After po administration of C. tubulosa extract (400 mg/kg), the in vivo metabolites in urine and fecal were obviously different in healthy and chronic unpredictable stress model rats. The metabolic ability to generate secondary glycosides and aglycones in depressive rat intestinal microbiota was much weaker than that in normal rat intestinal microbiota.…”
Section: Metabolites In Vivomentioning
confidence: 97%
“…Liquid chromatography coupled with tandem mass spectrometry (LC‐MS/MS) has recently become a powerful and reliable analytical technique for metabolite identification in vivo (Liu and others ; Luo and others ). Urine is recognized as an ideal biological matrix to investigate in vivo metabolic patterns (Hu and others ).…”
Section: Introductionmentioning
confidence: 99%